2005
DOI: 10.4049/jimmunol.175.11.7226
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human T Lymphocytes Engineered with a Codon-Optimized IL-15 Gene Resist Cytokine Withdrawal-Induced Apoptosis and Persist Long-Term in the Absence of Exogenous Cytokine

Abstract: IL-15 is a common γ-chain cytokine that has been shown to be more active than IL-2 in several murine cancer immunotherapy models. Although T lymphocytes do not produce IL-15, murine lymphocytes carrying an IL-15 transgene demonstrated superior antitumor activity in the immunotherapy of B16 melanoma. Thus, we sought to investigate the biological impact of constitutive IL-15 expression by human lymphocytes. In this report we describe the generation of a retroviral vector encoding a codon-optimized IL-15 gene. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 52 publications
1
70
0
Order By: Relevance
“…8 This retroviral vector contains the murine stem cell virus LTR and RNA processing signals similar to the MFG-class of retroviral vectors. The anti-MART-1 AIB TCR retroviral vector was used for control transductions.…”
Section: Generation Of the Lc15 Cell Line Vector Transduction And Cmentioning
confidence: 99%
“…8 This retroviral vector contains the murine stem cell virus LTR and RNA processing signals similar to the MFG-class of retroviral vectors. The anti-MART-1 AIB TCR retroviral vector was used for control transductions.…”
Section: Generation Of the Lc15 Cell Line Vector Transduction And Cmentioning
confidence: 99%
“…Although IL-2 plays a critical role in the stimulation of activated T cells, it is also involved in activationinduced cell death and the establishment of peripheral tolerance. Several studies have indicated that an alternative γ-chain cytokine, IL-15, provides potent homeostatic T-cell survival/proliferative signals, inhibits IL-2-mediated activation-induced cell death, and may be superior to IL-2 in immunotherapy applications (25,26). Recently, IL-15 has been shown to function in establishing the long-term persistence of adoptively transferred central memory T (T CM ) cells in primates, suggesting significant potential in T-cell therapy for cancer (27).…”
Section: A Clinically Relevant T-cell Proliferation System With Drug-mentioning
confidence: 99%
“…We can increase homing to tumor sites by expressing chemokine receptors specific for the molecules the tumors produce, while T cell expansion and persistence in the hostile tumor microenvironment can be increased by expressing transgenes that confer resistance to apoptosis, senescence, or inhibitory cytokines, or that provide autocrine T cell growth. 38 Any genetic strategy that enhances the survival of T cells, however, runs the risk of producing unwanted lymphoproliferation. Although protocols transferring genes to T cells have been safe to date, this strategy is being implemented with caution.…”
Section: Modification Of Effector T Cellsmentioning
confidence: 99%